2012
DOI: 10.1088/0964-1726/21/6/065006
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of wide bandwidth energy harvesting from vibrations

Abstract: We experimentally demonstrate a true wide bandwidth vibration energy harvester based on piezoelectric transduction. Our device is designed to work specifically off-resonance under sinusoidal input vibrations with constant displacement amplitudes. The same device displays wide bandwidth operation under vibrations with constant acceleration amplitudes. We have achieved over 6 nW of wide bandwidth power extraction per active piezoelectric patch between 80–180 Hz for constant 100 µm displacement amplitude, and acr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…The nonlinear PEH device provided a power bandwidth exceeding 50% of the center frequency and 2 orders of power magnitude improvement. The hardening nonlinearity induced by large deflections of four fixed-fixed piezoelectric beams with inertial proof mass has also been demonstrated by Huang et al 265 and Marinkovic and Koser, 266,267 which were shown to have a wide steady state response bandwidth.…”
Section: -18mentioning
confidence: 66%
“…The nonlinear PEH device provided a power bandwidth exceeding 50% of the center frequency and 2 orders of power magnitude improvement. The hardening nonlinearity induced by large deflections of four fixed-fixed piezoelectric beams with inertial proof mass has also been demonstrated by Huang et al 265 and Marinkovic and Koser, 266,267 which were shown to have a wide steady state response bandwidth.…”
Section: -18mentioning
confidence: 66%
“…Moreover, power generation performance of a EMSD working as an energy harvester is limited by resonance excitation as shown in [44]; therefore, other methods as multigenerator methods or multiresonance modes have to be applied. Marinkovic and Koser [45] showed wide bandwidth energy harvested from vibrations by using multigenerator method; however, its damping capacity at frequencies lower than 20 Hz is much reduced, acting as a bandwidth pass filter. Multiresonance mode method was used in [46] showing a device with 2 degrees of freedom that has two resonant peaks which may be tuned independently maintaining fairly uniform power output over a frequency range.…”
Section: Electromagnetic Shuntmentioning
confidence: 99%
“…Thus, traditional linear energy harvesters are usually limited to very narrow frequency ranges. In order to broaden the frequency bandwidth for effective energy harvesting, different techniques such as nonlinear energy harvesting [2,[18][19][20][21][22][23][24][25][26][27], array-harvester systems [28,29], and frequencytunable systems [30] have been developed so the harvester can accommodate a broader frequency range. Each technique has its own advantages and disadvantages.…”
Section: Introductionmentioning
confidence: 99%